Action research remodelled in a competitive, profit-oriented sector: teachers' and managers' perspectives. Issue 3 (26th May 2020) - Edwards, Emily; Ellis, Neville John
ABSTRACT: Action research has enjoyed phenomenal growth in the field of education as a catalyst for teacher professional learning with a view to school improvement, but it is commonly remodelled across various local settings. Adopting a Schatzkian perspective, this study investigates the experiences of a range of teachers engaging in an action research program in a competitive, profit-oriented setting – the English Language Intensive Courses for Overseas Students (ELICOS) sector in Australia – to explore how action research has been prefigured and remodelled in this unique context. A qualitative case study approach was adopted and a series of semi-structured interviews conducted with teachers and managers of ELICOS centres. Results of this study indicate that the way action research is understood and practised by teachers and managers in the ELICOS sector has been shaped by the competitive, profit-oriented context in which they function, with an emphasis on 'winning' and gaining status through action research.